The impact of agroecology training on the adaptability of smallholder communities to climate change in the Mopani district of Limpopo - Giliam, Amy Tarryn (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.